Determination of Bioactivity and Antimicrobial Activity of Bumblebee (Bombus terrestris L.) Brood Cover Wax Material - Erkan, C; Kara, Y; Keskin, M; Ertürk, Ö; Gösterit, A; Kolaylı, S (Journal of the Hellenic Veterinary Medical Society, 2022)
Bumblebee (Bombus terrestris L.) is a bee race that take part in pollination. It is though Bumblebee (Bombus terrestris L.) is only used in pollination. But, it is not only take part in pollination, it provide to produce different products. Nest cover wax material is a kind of bee product that produced by Bumblebee (Bombus terrestris L.). Although it is considered to be waste, nest cover wax material is an important hive product with its antioxidant and antimicrobial activities. In this study, Bumblebee nest cover wax material was produced under laboratory conditions in a controlled manner. Biochemical characterization of nest cover wax material obtained from five different colonies was performed and antimicrobial activities were determined. Accordingly, it was determined that the total phenolic content of the samples ranged between 3.778±0.165 and 9.504±0.353 mg GAE/g. In addition, it was observed that the samples were rich in p-coumaric acid, luteolin, quercetin, t-sinnamic acid, chrysin and pinocembrin components. It was determined that nest cover wax material, which also showed antimicrobial activity, had nearly equivalent activity to beehive products such as honey, pollen and bee bread. The data obtained show that nest cover wax material will be an alternative product for apitherapy applications.